THE CORRELATION BETWEEN KNOWLEDGE AND PERCEPTION OF YOUTH USERS OF VAPE TOWARDS VAPING BEHAVIOR IN BANGIL DISTRICT - Maqnun, Lu'lu'il; Lestari, Pudji; Wulandari, Laksmi (Journal of Community Medicine and Public Health Research, 2021)
The use of e-cigarettes year by year increases among adolescents. The increase correlates with their lack of knowledge about e-cigarettes and the perception that e-cigarettes are safer than conventional cigarettes. This research aims to analyze the relationship between the level of knowledge and perception of e-cigarettes to vaping behavior in adolescents in Bangil, Pasuruan. This study was analytic observational with a cross-sectional approach conducted from September until October 2019. The subjects in this study were 76 respondents selected by the purposive sampling method. The respondents were recruited from 3 cafes in Bangil by distributing questionnaires to those who met the inclusion criteria. The independent variables are the respondent's knowledge level and perception about e-cigarettes, while the dependent variable is vaping behavior. The data has been analyzed with Spearman's rho. From the analysis, there was a correlation between level of knowledge and vaping behavior with p=0.019 (p<0.05) and 0.269 correlation coefficient. Also, a correlation between perception and vaping behavior with p=0.000 (p<0.05) and 0.420 correlation coefficient. There was a correlation between knowledge level and perception of e-cigarettes to vaping behavior among adolescent users.